2016
DOI: 10.2147/ppa.s105624
|View full text |Cite
|
Sign up to set email alerts
|

Scale up use of family planning services to prevent maternal transmission of HIV among discordant couples: a cross-sectional study within a resource-limited setting

Abstract: BackgroundIntegration of family planning services (FPS) into human immunodeficiency virus (HIV) care for HIV-infected women is an important aspect of the global prevention of mother-to-child transmission (PMTCT) strategy. We assessed the integration of FPS into routine care of HIV-infected mothers by evaluating the uptake and barriers of contraception and PMTCT services.MethodsWe conducted an interventional study using the interrupted time series approach in the health care facilities located in Yaounde, Camer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
(37 reference statements)
2
9
0
1
Order By: Relevance
“…The review found that SCS were largely unavailable in sub-Saharan Africa outside of research settings, except for general availability (i.e., not for safer conception specifically) of ART and VMMC. Availability of SCS methods was greatest in public health facilities providing general services for people living with HIV [2026, 31, 36, 3944, 4750, 56, 58, 59, 62, 63, 6668]. More advanced or expensive strategies such as sperm washing, or PrEP remain unavailable in most public health facilities due to cost and lack of provider training [1417, 23].…”
Section: Discussionmentioning
confidence: 99%
“…The review found that SCS were largely unavailable in sub-Saharan Africa outside of research settings, except for general availability (i.e., not for safer conception specifically) of ART and VMMC. Availability of SCS methods was greatest in public health facilities providing general services for people living with HIV [2026, 31, 36, 3944, 4750, 56, 58, 59, 62, 63, 6668]. More advanced or expensive strategies such as sperm washing, or PrEP remain unavailable in most public health facilities due to cost and lack of provider training [1417, 23].…”
Section: Discussionmentioning
confidence: 99%
“…k These data were reported in the article of Kuete et al . (2016) . l The article of Mujugira et al .…”
Section: Methodsmentioning
confidence: 99%
“…Five of these were excluded because they remained unclarified, and two were excluded after the authors' clarification because they did not meet the eligibility criteria [44,45]. Because of overlapping samples, four articles ([46] and [47]; [48] and [49]) were considered as two studies. Priority was given to the articles of Beyeza-Kashesya et al [47] and Kuete et al [49].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Основными причинами прерывания беременности были: нежелательная беременность -50%, отсутствие материальных средств для самостоятельного существования, финансовая зависимость от партнера -28,5%, недостаточная информированность относительно возможности рождения здорового ребенка -21,5%. Невынашивание беременности (самопроизвольные аборты, неразвивающаяся беременность) выявлено у 21,5% ВИЧ-инфицированных женщин [5].…”
unclassified